2020
DOI: 10.1002/fsn3.1978
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional composition and antinutrient content of Heteromorpha arborescens (Spreng.) Cham. & Schltdl. leaves: An underutilized wild vegetable

Abstract: The nutritional and antinutrient composition of Heteromorpha arborescens (Spreng.) Cham. & Schltdl. leaves was reported in this study. Proximate analysis revealed the presence of 8.5% total ash, 4.92% crude fat, 8.41% moisture, 15.74% crude protein, 21.48% crude fiber, 40.95% carbohydrates, and 271.04 kcal/100 g energy value. Mineral analysis showed that H. arborescens leaves are very rich in K, Ca, and Fe. Considerable amounts of Mg, Mn, Na, P, Cu, and Zn were also present. Vitamin analysis showed that the pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 47 publications
0
9
1
Order By: Relevance
“…Literature is replete with information regarding the essentiality of fibre in food substances (Unuofin et al, 2017b;Adegbaju et al, 2019;Idris et al, 2019;Abifarin et al, 2021). Our findings revealed that ginger grown in Imo state, Nigeria had the highest crude fibre content (10.36 ± 0.67%) when compared with other geographical locations studied as shown in Table 1.…”
Section: Nutritional and Mineral Composition Of Ginger Rhizome From Different Geographical Locationmentioning
confidence: 68%
“…Literature is replete with information regarding the essentiality of fibre in food substances (Unuofin et al, 2017b;Adegbaju et al, 2019;Idris et al, 2019;Abifarin et al, 2021). Our findings revealed that ginger grown in Imo state, Nigeria had the highest crude fibre content (10.36 ± 0.67%) when compared with other geographical locations studied as shown in Table 1.…”
Section: Nutritional and Mineral Composition Of Ginger Rhizome From Different Geographical Locationmentioning
confidence: 68%
“…The calcium content in the leaves was higher than that reported in Heteromorpha arborescens (Spreng.) leaves by Abifarin et al, (2021). It supports the growth and maintenance of bones, teeth and muscles (Dinicolantonio et al, 2018).…”
Section: Anti-nutritional Analysismentioning
confidence: 99%
“…Sodium is engaged in the control of acid-base balance, normal cell function, and transport of metabolites, transmission of nerves impulse and maintaining blood pressure (Insel et al, 2011). Potassium is essential for sustaining normal cell function, regular muscle contraction, and blood pressure regulation (Abifarin et al, 2021).…”
Section: Anti-nutritional Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The moisture content in both fresh and dried materials was determined by the oven method at 105 °C, and protein content was detected according to the Kjeldahl method (Abifarin et al, 2021).…”
Section: Physiochemical Analysismentioning
confidence: 99%